The Insecurity of Afghan Refugees in Indonesia: An Overview from the Perspective of Human Security - Amin, Latifah (Malaysian Journal of International Relations, 2022)
This study aims to analyse the security conditions of Afghan refugees in Indonesia which specifically considers human security, and analyses why the insecurity conditions of refugees occur. Afghanistan’s domestic political crisis has resulted in humanitarian crisis which led to many civilians fleeing abroad to obtain security. As of June 2021, the number of Afghan refugees had reached 7,460 (57 percent) of the total refugees in Indonesia. Many news reports state that although Afghan refugees are ’safe’ from repression and conflict in Indonesia, their condition is not good or to be desired - which the author concludes as unsafe. Thus, this paper focuses on addressing the question as to ‘why are the conditions of Afghan refugees in Indonesia unsafe?’. This study uses a qualitative method of an explanatory type. Data are obtained through literature study. The analytical framework uses Human Security concept to explain the intended “unsafe conditions”. The author argues that, (1) Afghan refugees experience economic, food, health, individual, community and environmental security problems which are identified as insecurity conditions. (2) These conditions are caused by the status of Afghan refugees in Indonesia as illegal immigrants as the UNHCR has not been maximal in seeking comprehensive long-term solutions, in addition to the complexity of the resettlement process and limited funds for handling refugees.